In Vitro Expressed GPCR Inserted in Polymersome Membranes for Ligand‐Binding Studies1. Issue 2 (19th November 2012) - May, Sylvia; Andreasson‐Ochsner, Mirjam; Fu, Zhikang; Low , Ying Xiu; Tan, Darren; de Hoog, Hans‐Peter M.; Ritz, Sandra; Nallani, Madhavan; Sinner, Eva‐Kathrin
<x xml:space="preserve">Abstract</x> The dopamine receptor D2 (DRD2), a G‐protein coupled receptor is expressed into PBd22‐PEO13 and PMOXA20‐PDMS54‐PMOXA20 block copolymer vesicles (see scheme). The conformational integrity of the receptor is confirmed by antibody‐ and ligand‐binding assays. Replacement of bound dopamine is demonstrated on surface‐immobilized polymersomes, thus making this a promising platform for drug screening.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>